Mechanism of Influence of Soluble Fluorine on Mechanical Properties of α-Hemihydrous Gypsum - Lusong WANG; Xianbo LI; Weifan DU; Wenxin GAO (Kuangchan zonghe liyong)
This is an article in the field of mineral materials. The preparation of α-hemihydrate gypsum from phosphogypsum instead of natural gypsum is an important way of its high value-added utilization. However, soluble fluorine impurities in phosphogypsum will have adverse effects on α-hemihydrate gypsum. In this article, the effect of soluble fluorine on the setting time and the strength of the hardened body of α-hemihydrate gypsum was studied, and its mechanism was explored by XRD, SEM-EDS and XPS. The results show that soluble fluorine can shorten the setting time and decrease the mechanical strength of α-hemihydrate gypsum. The microstructure analysis of hardened body shows that soluble fluorine can coarsen the particles of gypsum dihydrate, increase the internal pores, and reduce the mechanical strength. XRD and XPS analysis show that soluble fluorine reacts with Ca2+ generated by the dissolution of α-hemihydrate gypsum to form calcium fluoride with smaller solubility product, thus shortening the setting time of α-hemihydrate gypsum.